Actions to transform food systems under climate change: Shift to healthy and sustainable climate-friendly diets - Transforming Food Systems Under a Changing Climate Initiative (2020)
Transforming Food Systems Under a Changing Climate is an initiative that aims to identify high-priority actions for food systems to both adapt to climate change and reduce emissions, while not losing sight of the many other functions of, and challenges to, our food systems. The action described in this briefing is one of 11 transformative actions that should take priority. Consumption of beef and dairy is the largest single driver of agricultural greenhouse gases (GHGs) globally. The challenge is to incentivize dramatic reductions in beef and dairy consumption in 15 high- and middle-income countries and all C40 cities by 2030. Shifting globally to diets with less red meat has been estimated to reduce emissions by up to two thirds, reduce health costs and save up to 8 million lives.